Millennial‐scale oscillations and an environmental regime shift around the Middle to Late Holocene transition in the North Atlantic region based on a multiproxy record from Isfjorden, West Spitsbergen - Brice, Camille; De Vernal, Anne; Francus, Pierre; Forwick, Matthias; Nam, Seung‐Il (Boreas, 2023)
Palynological and sedimentological analyses were performed on the sediment core HH16‐1205‐GC retrieved from the central Isfjorden, West Spitsbergen. The sequence, which spans the last 7000 years, revealed an overall cooling trend with an important climate shift between 4.4 and 3.8 cal. ka BP, in addition to millennial‐scale oscillations. Sea‐surface reconstruction from dinocyst assemblages indicates a decrease in summer sea‐surface temperature, from 2.5 to 1.5 °C, and primary productivity, from 750 to 650 gC m −2 a −1 over the last 7000 years. From around 6.8 to 5.8 cal. ka BP, the sedimentological and palynological data suggest a predominant sediment supply from the inner part of the fjord, ice rafting, dense sea ice cover, strongly stratified water masses and high primary productivity. The interval from 4.4 to 3.8 cal. ka BP is marked by a layer of coarser material and a significant decrease in the grain‐size mode. Our geochemical data show large‐amplitude fluctuations after 2.0 cal. ka BP, while an increase in the dinocysts Impagidinium pallidum and Spiniferites elongatus from 2.0 to 1.2 cal. ka BP suggests enhanced Atlantic Water inflow. The dinocyst‐based reconstructions also reveal large‐amplitude millennial fluctuations in sea ice cover, summer sea‐surface temperature and salinity. Wavelet analysis and cross‐wavelet analysis on K/Ti ratio coupled with sea‐ice estimates confirm a strong signal with a periodicity of 1200–1500 years.